2003
DOI: 10.1590/s1415-47572003000300018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic variability within and among coffee progenies and cultivars using RAPD markers

Abstract: The RAPD technique associated with restriction digestion of genomic DNA was used to assess the genetic variability within and among nine populations of Coffea arabica, including six progenies belonging to the Sarchimor germplasm, the progeny PR 77054-40-10 (Catuaí Vermelho IAC 81 x Icatu), and two commercial cultivars (IAPAR 59 and Catuaí Vermelho IAC-81). These populations were evaluated using analysis of molecular variance (AMOVA), genetic similarity among progenies, and percentage of polymorphic loci. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…In wheat genotypes, Koebner (1995) observed that digestion of template DNA prior to PCR amplification allowed for more efficiency of primer annealing along shorter DNA fragment, where a simplified secondary structure was less likely to interfere with the process. Similar results were obtained by Sera et al (2003) in 14 accessions of arabica coffee and by Silveira et al (2003) in a study of genetic variability within and among Sarchimor progenies.…”
Section: Resultssupporting
confidence: 83%
“…In wheat genotypes, Koebner (1995) observed that digestion of template DNA prior to PCR amplification allowed for more efficiency of primer annealing along shorter DNA fragment, where a simplified secondary structure was less likely to interfere with the process. Similar results were obtained by Sera et al (2003) in 14 accessions of arabica coffee and by Silveira et al (2003) in a study of genetic variability within and among Sarchimor progenies.…”
Section: Resultssupporting
confidence: 83%
“…In the genus Coffea, several studies have shown the efficiency of RAPD markers for the genotype characterization, assessment and identification and for genetic mapping (Maluf et al 2005, Teixeira-Cabral et al 2004, Silveira et al 2003, Fontes et al 2000, Lashermes et al 1996, OrozcoCastillo et al 1994. A disadvantage of this marker type is its dominance, which impairs the distinction of polymorphism of heterozygous from homozygous dominant genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Different lines of HDT have been used worldwide to breed coffee varieties that are resistant to different pathogens. As would be expected, different accessions of HDT derivatives have different levels of introgressed C. canephora genome Silveira et al, 2003). This could explain the close relationship observed between HDT, Ruiru 11 and Catimor Line 90 to Robusta.…”
Section: Discussionmentioning
confidence: 55%